An Experimentally Established Key Intermediate in Benzene Nitration with Mixed Acid. (25th September 2015) - Koleva, Gergana; Galabov, Boris; Hadjieva, Boriana; Schaefer, Henry F.; Schleyer, Paul von R.
Abstract: Experimental evidence is reported for the first intermediate in the classic SE Ar reaction of benzene nitration with mixed acid. The UV/Vis spectroscopic investigation of the reaction showed an intense absorption at 320 nm (appearing as a band shoulder) arising from a reaction intermediate. Our theoretical modeling shows that the interaction between the two principal reactants with solvent (H2 SO4 ) molecules significantly affects the structure of the initial complex. In this complex, a larger distance between the aromatic ring and nitronium ion precludes the possibility for electronic charge transfer from the benzene π‐system to the electrophile. The computational modeling of the potential energy surface reveals that the reaction favors a stepwise mechanism with intermediate formation of π‐ and σ‐ (arenium ion) complexes. Abstract : Alte Reaktion – neue Zwischenstufe : Das erste Intermediat der Benzolnitrierung mit einer Säuremischung wurde experimentell nachgewiesen. Experiment und Theorie stimmen darin überein, dass die Bildung des π‐Komplexes nicht mit einem Ladungstransfer einhergeht. EOM=Bewegungsgleichung.